Food Forward : how volunteer teams move surplus produce from tree to table - Silver, Nora (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2021)
Food Forward's volunteers call it "fruit therapy" to harvest excess fruit from citrus trees throughout Los Angeles knowing it will soon feed food insecure families. Through all of the nonprofit's surplus produce programs in 2020, the team rescued 62.5 million pounds of nutritious fruits and vegetables, fed well over one-million people, and even organized 2,037 socially-distanced volunteer events during the COVID-19 shut-downs. The team, comprising 37 engaged staff and 4,100 dedicated volunteers, worked together to overcome the imbalance of food waste and people who lacked enough to eat. How did Food Forward maintain and motivate such a large volunteer group to help bridge the hunger gap-and what role would they play in the organization's future?
Orginally Published InSilver, N. (2021). Food Forward: How Volunteer Teams Move Surplus Produce from Tree to Table. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Food security -- Case studies; Volunteers -- Case studies